Quality Assurance Model for Non-formal Institutions at Community Learning Center Al-Madinah, Kediri City - Abdurochman Abdurochman; Zulkarnain Zulkarnain; Hardika Hardika; Ahmad Ahmad; abd Latif Bustami (KOLOKIUM Jurnal Pendidikan Luar Sekolah, 2023)
This article examines the quality assurance model implemented by Community Learning Center (CLC) Al-Madinah in Kediri City. This research uses a qualitative approach with a case study method. Research data was collected through observation, interviews and documentation techniques. Research data was analyzed using an interactive analysis model. The research results show that CLC Al-Madinah implements an internal quality assurance model that is participatory, collaborative and sustainable. This internal quality assurance model includes four stages, namely planning, implementation, assessment and improvement. This internal quality assurance model has several advantages and disadvantages that need to be considered and improved by CLC Al-Madinah and other non-formal institutions. This research provides several recommendations for CLC Al-Madinah and other non-formal institutions in improving the quality of educational services. This study also has several limitations that need to be addressed by future research.